Energy-Efficient Analog Beamforming with Short Packets in Millimeter-Wave MIMO Systems - Borras, Jordi; Molina, Francesc; Lopez-Valcarce, Roberto; Sala-Alvarez, Josep (Conference record - Asilomar Conference on Signals, Systems, & Computers, 2020)
The energy-aware design of fully analog precoders and combiners is investigated in this paper. To that aim, we consider a millimeter-wave short-packet communication scenario where power consumption and hardware complexity constitute relevant factors. User terminals employ a single channel encoder and, at hardware level, they implement analog architectures that combine phase shifters and switches. Additionally, transmitting terminals also leverage a power control system. An energy efficiency figure of merit is considered, and its optimization subject to finite packet-length constraints is tackled cyclically over disconnected feasible sets. Numerical results are reported firstly, to illustrate the advantages of the proposed short-packet fully analog design, secondly, to compare its performance to that of on-off beamforming, and finally, to discuss the optimality of proposed optimization algorithm.